Creative webs: decoding the creativity potential of Twitter followers - Hayat, Tsahi (Frontiers in Psychology, 2024)
Previous studies have associated creativity to one's social networks. This study builds on this framework and examines the premise that one's social fabric is a catalyst for creativity, specifically probing the dynamics between online social connections and creative expressions in the realm of ESports. Therefore, this research paper examined a correlation between people's creativity and their Effective Network Size (non-redundant ties) on Twitter, to see if potentially non-redundant information is related to creativity. Creativity score was defined as the propensity of a participant to utilize specific terms relating to Esports in its emerging stages, prior to its peak popularity as evidenced by Google Trends. Effective Network Size was analyzed based on the social ties of participants on Twitter (N=50,000). The findings indicate that the higher the Effective Network Size score, the higher the creativity score. Furthermore, geographically dispersed social networks moderated the relationship between Effective Network Size and creativity. For people with more dispersed social networks, ENS was more constructive for creativity. These findings are discussed in the broader context of the relevancy of online social networking sites for creativity.